2020
DOI: 10.1016/j.amjmed.2019.05.047
|View full text |Cite
|
Sign up to set email alerts
|

Relation of Kidney Function Decline and NT-proBNP With Risk of Mortality and Readmission in Acute Decompensated Heart Failure

Abstract: Background-Acute declines in kidney function occur in approximately 20-30% of patients with acute decompensated heart failure, but its significance is unclear and importance of its context is not known. This study aimed to determine the prognostic value of a decline in kidney function in the context of decongestion among patients admitted with acute decompensated heart failure. Methods-Using data from patients enrolled in the Ultrafiltration in Decompensated Heart Failure with Cardiorenal Syndrome Study (CARRE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
32
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 35 publications
0
32
0
2
Order By: Relevance
“…Measurements of kidney function obtained outside of these prespecified protocol visits were excluded, as indication for testing was unclear. Given the known variability in kidney function during in-hospital treatment for acute HF and the fact that the relation of short-term declines in kidney function with outcomes is controversial, 5 , 6 , 34 only kidney endpoints occurring after discharge from the initial hospitalization were included in the primary analysis. In order to avoid short-term perturbation in hemodynamics that resulted in reaching the kidney outcomes, reaching the kidney endpoint required 2 consecutive measures of eGFR.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Measurements of kidney function obtained outside of these prespecified protocol visits were excluded, as indication for testing was unclear. Given the known variability in kidney function during in-hospital treatment for acute HF and the fact that the relation of short-term declines in kidney function with outcomes is controversial, 5 , 6 , 34 only kidney endpoints occurring after discharge from the initial hospitalization were included in the primary analysis. In order to avoid short-term perturbation in hemodynamics that resulted in reaching the kidney outcomes, reaching the kidney endpoint required 2 consecutive measures of eGFR.…”
Section: Methodsmentioning
confidence: 99%
“…Reduced levels of kidney function are highly prevalent among patients with HFrEF and are associated with adverse clinical outcomes. 1 , 2 , 3 , 4 Acute declines in kidney function, such as during hospitalizations or after starting certain medications, may or may not be associated with worse clinical outcomes 5 , 6 ; however, longer-term declines in kidney function are consistently associated with increased risk for mortality and cardiovascular outcomes in HFrEF. 7 , 8 Few studies have examined risk factors for longitudinal declines in eGFR among patients with HFrEF.…”
mentioning
confidence: 99%
“…However, the complex relationship between change in renal function and outcomes among patients with AHF complicates matters. A temporary in‐hospital decline in eGFR appears to portend better outcomes as long as it is accompanied by effective decongestion 5,6 . For the patients in this study 3 several questions remain unanswered: What events occurred in the hospital?…”
mentioning
confidence: 92%
“…A temporary in-hospital decline in eGFR appears to portend better outcomes as long as it is accompanied by effective decongestion. 5,6 For the patients in this study 3 several questions remain unanswered: What events occurred in the hospital? What medications or other treatments were administered?…”
mentioning
confidence: 99%
“…1−3 The article by McCallum et al is the latest of this long series. 4 The authors have combined data from patients enrolled in the Cardiorenal Rescue Study in Acute Decompensated Heart Failure (CARRESS-HF) and Diuretic Optimization Strategies Evaluation (DOSE) trials to explore the prognostic impact of rise in serum creatinine in the setting of acute heart failure therapy. They, too, found that increase in serum creatinine was not associated with adverse outcomes, whereas decongestion (measured through decrease in N-terminal pro-b-type natriuretic peptide [NT-proBNP]) showed a 31% reduction in the rate of death and hospital readmission.…”
mentioning
confidence: 99%